Role of hysteroscopy and histopathology in evaluating patients with abnormal uterine bleeding - Firdous, Nighat; Mukhtar, Samar; Bilal, Sheikh; Beigh, Salma Kounsar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding is one of the leading causes for seeking gynaecological advice. The aim and objectives of the study was to determine the pattern of hysteroscopic abnormalities and histopathological features of Abnormal Uterine Bleeding and to correlate hysteroscopic findings with histopathological findings. Methods: The present study “Role of Hysteroscopy and Histopathology in Evaluating patients with Abnormal Uterine Bleeding” was an observational study carried out in the Postgraduate Department of Obstetrics and Gynaecology and Postgraduate Department of Pathology of Government Medical college, Srinagar after obtaining clearance from the institutional ethical committee. The period of the study was One and a Half Years from April 2014 to September 2015. Results: The most common abnormality detected by hysteroscopy was Endometrial Hyperplasia (27 cases, 27%) followed by endometrial polyps (21 cases, 21%). Endometrial Hyperplasia was the most common abnormality found in Menorrhagia followed by polyps while polyps were the most common finding in polymenorrhea and endometrial hyperplasia was the most common pathology in postmenopausal bleeding. Hysteroscopy had a sensitivity of 93.2%, specificity of 83.9%, positive predictive value of 82%, Negative Predictive Value of 94% in diagnosing etiology of abnormal uterine bleeding. Conclusions: This study confirms that hysteroscopy has a definitive role in evaluating patients with abnormal uterine bleeding and hysteroscopy and histopathology complement each other in the evaluation of a patient with Abnormal uterine bleeding.